Metagenomic insights into the effects of Chive seed flavonoid on intestinal fermentation, morphology, and microbiota composition in sheep - Li, Xujie; Li, Dengpan; Wang, Chunhui; Li, Qiao; Nie, Yajing; Zhang, Liming; Xu, Jin; Ma, Youji (Frontiers in Microbiology, 2025)
Chive seed flavonoid (CSF) exhibits antioxidant, digestive, and immunomodulatory properties, yet their effects on ruminant intestinal development and microbial ecosystems remain underexplored. This study systematically evaluated CSF supplementation (0.25% of concentrate) on intestinal morphology, volatile fatty acids (VFAs) dynamics, and microbiota composition in 16 weaned Hu lambs (3 months; 19.57 ± 1.56 kg initial weight) using histomorphometry, VFA quantification, and full-length 16S rRNA sequencing. Animals were randomly allocated to a control (basal diet) or CSF-supplemented group (T), following a 7-day adaptation and 90-day experimental protocol. Key findings revealed: (1) The T group demonstrated increased jejunal and ileal villus length (p < 0.05), elevated villus height-to-crypt depth ratio (V/C; p < 0.05), thickened muscular layers (p < 0.05), and reduced crypt depth (p < 0.05). (2) CSF supplementation significantly elevated acetate, propionate, butyrate, and total VFAs (p < 0.05) in ileum, cecum, colon, and rectum, with notable jejunal propionate and total VFAs increases (p < 0.05). (3) Upregulated expression of ileal and cecal genes (IGF1, CD81, CTNNBL1, SLC39A8) linked to tissue morphogenesis and VFAs absorption was observed in the T group (p < 0.01). (4) Full-length 16S analysis demonstrated CSF-enhanced microbial diversity and selective enrichment of Cyanobacteriota, Bacillus, Acetobacterium, and Streptomyces [Linear Discriminant Analysis Effect Size (LEfSe) analysis]. Regional microbial shifts included Bacteroidota proliferation in the small intestine and rectum, Actinomycetota dominance in duodenum/cecum/colon, and ileal enrichment of Bacillota, Clostridium, and Streptomyces. KEGG pathway analysis confirmed CSF-driven enhancements in carbohydrate/energy metabolism, immune regulation, and intestinal barrier pathways (p < 0.05). In conclusion, dietary supplementation with 0.25% CSF improved intestinal morphology, increased the production of VFAs, and optimized microbial composition, thereby promoting intestinal health in sheep. This study provides a theoretical basis for the application of CSF in promoting healthy production in sheep.